2009
DOI: 10.1016/j.acra.2008.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal Texture Analysis in Digital Breast Tomosynthesis for Breast Cancer Risk Estimation

Abstract: Rationale and Objectives-Studies have demonstrated a relationship between mammographic parenchymal texture and breast cancer risk. Although promising, texture analysis in mammograms is limited by tissue superimposition. Digital breast tomosynthesis (DBT) is a novel tomographic xray breast imaging modality that alleviates the effect of tissue superimposition, offering superior parenchymal texture visualization compared to mammography. Our study investigates the potential advantages of DBT parenchymal texture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 64 publications
(95 reference statements)
3
35
1
Order By: Relevance
“…In our study, we found our semi-automated CT density measurements agreed with subjective mammographic assessments in up to 84.4% of cases, with only one level difference in the rest. Similar results to ours were found in other studies involving three-dimensional imaging techniques such as tomosynthesis 13 and dedicated breast CT, 14 which had better inter-reader variation than twodimensional techniques.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, we found our semi-automated CT density measurements agreed with subjective mammographic assessments in up to 84.4% of cases, with only one level difference in the rest. Similar results to ours were found in other studies involving three-dimensional imaging techniques such as tomosynthesis 13 and dedicated breast CT, 14 which had better inter-reader variation than twodimensional techniques.…”
Section: Discussionsupporting
confidence: 81%
“…20,50,52 Cumulus has shown a strong positive correlation between parenchymal texture features and breast density with DBT (r 5 0.73); 50 such texture features were shown to be more related to mammographic breast density with DBT than with DM. Cumulus estimated mammographic density values are lower on DBT than on DM; 20,50,52 however, the software has been shown to overestimate breast density by 3% with DBT relative to DM in another study. 20 Reported Cumulusassessed mammographic breast density correlation between DBT and DM ranged from r 5 0.76 to 0.97 and r 5 0.78 to 0.91.…”
Section: Semi-automated Methodsmentioning
confidence: 99%
“…By combining information from different projections, DBT improves the differentiation of the adjacent anatomical structures, alleviating the superimposition effect [13]. More recent studies indicate about 30% increased DBT sensitivity and specificity compared with DM [14], with a 40% reduction in callback in screening [15-18].…”
Section: Introductionmentioning
confidence: 99%